Microarrays in the study of the basic mechanisms of evolution - Gibson, Greg (Henry Stewart Talks, 2009)
Gene expression profiling has quickly emerged as an important tool in the study of evolutionary biology, Many of the statistical methods used in quantitative genetics have been adopted for general use in microarray analysis, while advances in comparative genetics through genome sequencing have enabled comparative functional studies within and among species, The methodological issues and approaches to microarray-based studies in the context of evolution, Key studies that have shed light on the conservation and divergence in gene expression between species, Mechanisms of speciation and hybrid incompatibility, Natural selection and adaptation, Linking genotypes to phenotypes via gene expression, Ecological genetics, Emerging new types of microarray, and the novel questions they may be used to address
Archived at 2021/02/25